Antebrachial Deformity Correction Combined with Osteotomized Pancarpal Arthrodesis Using Patient-Specific Guides and a Custom Printed Implant in a Dog - Stork, Christoph K.; Petite, Audrey F. B.; Scutt, Adam J. L.; Oxley, Bill (VCOT Open, 2025)
This case report describes individualized treatment for a 4-year-old, 26 kg, Labrador–Springer crossbreed dog affected by chronic antebrachial growth deformity (ABGD) and recent acute carpal hyperextension injury. On the basis of a CT scan, patient-specific osteotomy guides (PSG) were designed for a diaphyseal radial ostectomy to correct the ABGD, as well as for distal radial and proximal radiocarpal and ulnar carpal bone ostectomies to arthrodese the antebrachiocarpal joint. A patient-specific 3D-printed titanium alloy implant (PSI) was applied to the dorsal aspect using the PSG pin holes as screw holes and the entire plate as a reduction device. Distally, the plate was applied to metacarpal bones II, III, and IV. At 2-month follow-up, the patient had returned to normal function, all implants were stable, and at 13 months, bone fusion was documented radiographically. When performing pancarpal arthrodesis, one might consider ostectomies (rather than burring) to increase the area of cancellous bone contact. Additional potential advantages of a PSG-PSI system include accurate limb alignment, improved distal fixation, and reduced surgical time. Carefully planned and executed single-session ABGD-correction and PCA resulted in an excellent long-term outcome in this large breed dog.
Keywords: antebrachial growth deformity; pancarpal arthrodesis; patient-specific osteotomy guides; patient-specific implant; dog